Technical Considerations in Primary Repair of a Congenital Prostatic Rectourethral Fistula in an Adult-Sized Patient - Timothy F. Tirrell; Farokh R. Demehri; Prathima Nandivada; Erin R. McNamara; Belinda Hsi Dickie (Georg Thieme Verlag KG, 2022)
Congenital anorectal malformations are generally diagnosed and repaired as a neonate or infant, but repair is sometimes delayed. Considerations for operative repair change as the patient approaches full stature. We recently encountered a 17-year-old male with an unrepaired congenital rectourethral fistula and detail our experience with his repair. We elected to utilize a combined abdominal and perineal approach, with robotic assistance for division of his rectourethral fistula and pullthrough anoplasty. Cystoscopy was used simultaneously to assure full dissection of the fistula and to minimize the risk of leaving a remnant of the original fistula (also known as a posterior urethral diverticulum). The procedure was well tolerated without complications. His anoplasty was evaluated 60 days postoperatively and was well healed without stricture. At 9 months of follow-up, he has good fecal and urinary continence. Robotic assistance in this procedure allowed minimal perineal dissection while ensuring precise rectourethral fistula dissection. The length of the intramural segment of the fistula was longer than anticipated. Simultaneous cystoscopy, in conjunction with the integrated robotic fluorescence system, helped reduce the risk of leaving a remnant of the original fistula.